Impact of VIP and cAMP on the regulation of TNF-alpha and IL-10 production: implications for rheumatoid arthritis. - Foey, A; Field, S; Ahmed, S; Jain, A; Feldmann, M; Brennan, F; Williams, R (BioMed Central, 2003)
Vasoactive intestinal peptide (VIP) is an anti-inflammatory immunomodulatory neuropeptide with therapeutic potential demonstrated for collagen-induced arthritis. The aim of this study was to characterise its potential anti-arthritic effect on human monocytes, macrophages, T cells, and rheumatoid arthritis synovial membrane cells. Monocytes, macrophages, and T cells derived from human peripheral blood were treated with VIP and compared with other cAMP-elevating drugs for a range of activating stimuli. Cytokine production was assessed for cell cultures and, in addition, the ability of VIPs to activate cAMP response element binding protein. VIP partially suppressed monocyte- and macrophage-derived tumour necrosis factor alpha (TNF-alpha) with no effect on IL-10, whereas VIP fails to regulate IL-10 and TNF-alpha production by T lymphocytes. No such modulation of cytokine profile was observed for rheumatoid arthritis synovial membrane cells. Elevation of intracellular cAMP, on the other hand, potently suppressed macrophage TNF-alpha production and modulated T-cell response by inhibiting TNF-alpha and IFN-gamma. VIP's lack of effect on IL-10 and its slight effect on TNF-alpha results from cAMP being rapidly degraded as the phosphodiesterase IV inhibitor, rolipram, rescues cAMP-dependent activation of cAMP response element binding protein. Interestingly, macrophages stimulated with phorbol 12-myristate 13-acetate/ionomycin displayed an augmented IL-10 response upon addition of dibutyryl cAMP, with corresponding downregulation in TNF-alpha, suggesting a complex interaction between protein kinase C and protein kinase A in cytokine regulation. In conclusion, VIP may represent an efficaceous anti-arthritic treatment modulating macrophage and T-cell cytokine profiles when used alongside a phosphodiesterase inhibitor.